Pemetaan Penyebaran Penyakit Endemik Di Provinsi Bali - Sukarsa, I Komang Gde; Kencana, I Putu Eka Nila (Jurnal Matematika; Vol 14 No 2 (2024)DO - 10.24843/JMAT.2024.v14.i02.p177, 2024)
The health sector is still the main concern of the people in Bali Province, especially the spread of endemic diseases. Bali Province has a fairly high number of endemic disease cases. Therefore, mapping of the spread of endemic diseases was carried out in each district in Bali Province using correspondence analysis. This research uses secondary data obtained from the health departement of each district in Bali Province. The analysis result show that in 2018 and 2022, the sub-districts that have a tendency towards pulmonary tuberculosis are Negara, West Selemadeg, Gianyar, Dawan and Banjar sub-districts. Dengue hemorrhagic fever tends to occur in the districts of Jembrana, Blahbatuh, Klungkung and Sukasada. Diarrhea tends to occur in the districts of Melaya, Pekutatan, Mendoyo, Selemadeg, Marga, Pupuan, Baturiti, East Selemadeg, Mengwi, Petang, Abiansemal, Tegalalang, Ubud, Tampaksiring, Payangan, Banjarangkan, Nusa Penida, Kintamani, Sidemen, Rendang, Selat, Sawan, Gerogak, Seririt, and Busungbiu. Malaria in several districts does not have a trend pattern. Keywords : correspondence analysis, endemic disease, subdistrict